UNDERSTANDING SERPIN POLICY AS AN INTERNAL MOBILITY PROGRAM IN KAZAKHSTAN: CASES OF STAKEHOLDERS’ IMPLEMENTATION AND INTERPRETATION OF THE POLICY WITHIN THREE UNIVERSITIES - Ivatov, Serik (Graduate School of Education, 2022)
Local actors play a crucial role in policy implementation as their actions may affect policy success. Although there has been the proliferation of studies on policy implementation and interpretation, there is the relative lack of empirical research on how local actors make sense of and implement policies in higher education. In addition, most of the extant studies has been done in countries with a decentralized higher education system, overlooking countries with a transitional higher education system. Therefore, the purpose of this study is to explore how university officials (vice-rectors, deans, heads, faculty members) interpret and implement the Serpin policy in Kazakhstan that has the transitional system. This study employed exploratory sequential mixed methods research design that contains two phases: qualitative, that has higher priority, followed by quantitative. In the first phase, I first explored through document analysis and one-on-one interviews how the policy is framed and implemented at the central level so that these data could be used as a baseline. Then, using this baseline, I explored through document analysis and semi-structured interviews how university officials make sense of and implement the policy, and what affects their sensemaking. In the second phase, I investigated the projected outcomes of the university officials’ implementation of the policy as perceived by the Serpin students, employing a survey developed based on the qualitative findings. The participants of this study included 25 university officials from three universities, one policymaker, and 295 undergraduate students. The study has several main findings. First, the state narrative of the Serpin policy included the description of its goals, problems it aims to address, and the image of the target population. Also, the Ministry of Education and Science is implementing the Serpin program, using an educational grant, which does not imply mandatory employment in the region of study, as a policy instrument. Second, university officials’ understanding of the Serpin policy diverged from state messaging, illustrating their synthesis of state and local messaging into a locally driven narrative. In addition, university officials did not make any changes in their practices to achieve the program’s goals, demonstrating satisficing implementation behavior. They did not offer specialized services or support for the Serpin students. This approach appears not to be fully effective in producing the main expected policy outcome, namely the retention of the Serpin graduates in the region of their higher education provider. Third, university officials’ sensemaking was most influenced by power (the interaction with powerful actors), followed by a lesser degree, the perception of region, the interaction with target population, the perception of institution, personal beliefs and experiences, institutional leadership, the interaction with employers, and the perception of existing policies. It can be concluded that local actors in transitional systems can be active policy sense-makers but passive policymakers. Their discretion to decide how to implement policies handed down from above may directly affect the achievement of expected policy outcomes.
Keywords: Type of access: Restricted; education policy; higher education; policy interpretation; policy implementation; sensemaking; street-level bureaucrats